Potent, non-covalent reversible BTK inhibitors with 8-amino-imidazo[1, 5-a]pyrazine core featuring 3-position bicyclic ring substitutes. Issue 17 (1st September 2020) - Liu, Jian; Guiadeen, Deodial; Krikorian, Arto; Gao, Xiaolei; Wang, James; Babu Boga, Sobhana; Alhassan, Abdul-Basit; Yu, Wensheng; Selyutin, Oleg; Yu, Younong; Anand, Rajan; Xu, Jiayi; et al.
Graphical abstract: Abstract: Bruton's tyrosine kinase (BTK) is a Tec family kinase with a well-defined role in the B cell receptor (BCR) pathway. It has become an attractive kinase target for selective B cell inhibition, and for the treatment of B cell related diseases. Many BTK inhibitors have been discovered for the treatment of cancer and rheumatoid arthritis, including a series of BTK inhibitors based on 8-amino-imidazo[1, 5- a ]pyrazine we recently reported. The X-ray crystal structures of BTK with inhibitors were also published, which provided great help for the SAR design. Here we report our SAR work introducing ring constraints for the 3-position piperidine amides on the BTK inhibitors based on 8-amino-imidazo[1, 5- a ]pyrazine. This modification improved the potency in BTK inhibitions, as well as the PK profile and the off-target selectivity. The dose-dependent efficacy of two BTK inhibitors was observed in the rat collagen induced arthritis (CIA) model.